DIDACTIC FOUNDATIONS FOR DEVELOPING STUDENTS’ COGNITIVE ACTIVITY IN DRAWING EDUCATION (Web of Teachers: Inderscience Research, 2025)
The article analyzes didactic approaches aimed at developing students’ cognitive activity in drawing education. The study highlights the role of interactive methods, practical modeling, and modern digital technologies in the formation of intellectual processes such as graphic literacy, spatial imagination, and analysis-synthesis skills. Additionally, it substantiates pedagogical factors that promote students’ motivation, independent inquiry, and creative thinking.